Education department policy constructions within highly political contexts: a critical policy study of multiculturalism. Issue 6 (2nd November 2022) - Sullivan, Anna; Tippett, Neil; Manolev, Jamie; Baak, Melanie; Johnson, Bruce
ABSTRACT: This article provides a critical analysis of policies from two education systems that support the education of students from migrant backgrounds. This analysis examines the highly political policy context of multiculturalism to reveal how education systems acquiesce to or resist social and political forces. In making this case, the article presents an historical analysis of the Australian federal government's multicultural policy and the events that shaped it. The article then presents an analysis of the national policy statement Multicultural Australia: United, Strong, Successful to understand the current federal position on multiculturalism. These analyses provide an understanding of the political rationality of the broader context. This article argues that education policy constructions are likely to reflect this political rationality. Against this backdrop it then examines primary policies from two education systems that relate to education for students from migrant and refugee backgrounds. The key argument is that, whilst the federal government attends to concerns about security, social integration and economic contributions, education departments can 'resist' and attend to broader issues related to educational equity and social justice.